Discrete Element Method Approach to Simulate Cracks in Four-Point Flexural Test - Faqih Ma arif; Slamet Widodo; Maris Setyo Nugroho; Zhengguo Gao (Kadiri University, 2023)
Concrete is a material that is widely used in construction. Concrete research efforts are ongoing and through a series of experimental tests. On the other hand, experimental tests require a lot of money, take a long time, and create waste. Several studies have revealed that numerical testing can accurately test concrete to fractures. However, modeling for the four-point load flexure test pattern is still not widely discussed. This study aimed to model the four-point flexural test of concrete using the discrete element method (DEM) approach. Sieve gradation was performed to determine particle size, and flexure testing was performed to calibrate the DEM model. DEM flexure testing was made using Yet Another Dynamic Engine (YADE) software with ASTM D6272 reference and beam dimensions 105 x 105 x 535 mm. The cohesive contact model with spherical particles is used, and the algorithm developed modifies the faceted sphere of interaction. The study results revealed that DEM can simulate crack behavior in flexural testing of unreinforced concrete. The DEM results show only a 2.13% difference in the experimental results of the flexural strength test. Meanwhile, crack behavior can be observed directly in the DEM simulation. The results of this study can be used to predict the failure pattern of the flexural test structure and to design the right proportion of the mixture to match the desired flexural strength. So that material efficiency and concrete flexure testing time can be achieved.